Control de inventarios y su influencia en la rentabilidad de ADROSES en la ciudad de Latacunga, provincia de Cotopaxi, año 2020-2021. - Lema Palango, Angélica Maribel (2021)
ADROSES is a family business directed by Eng. Adrián Heredia where they are dedicated to the production and export of good quality flowers. It is located in the Joseguando Bajo parish, coming to work in the Ecuadorian flower market providing quality products to important clients in the world, mainly in the North American market. The objective of the research is to propose an inventory control system that influences profitability by improving purchases. It is proposed as a hypothesis of the investigation, if inventory control affects profitability. The methodology used was established with a mixed quali-quantitative approach, the field, bibliographic and documentary research modality, the level or time of the deductive research, the information collection instruments were applied to the General Manager and the Head of Production. The factors that they directly or indirectly include for its growth in all areas will be determinedly analyzed. Therefore, this work was developed for a better inventory control, therefore, the system to be applied would be the inventory control by the FIFO method since the merchandise will be in constant entry and exit to different parts of the world. Through inventory control we can identify the activities, critical processes of the logistics operation, maximum and minimum quantities for stock of your warehouses, rotation, duration of inventory accuracy. It is also observed that with inventory control profitability increases.